Assessment of the hazard risk of the Metsamor Nuclear Power Plant (NPP) in Nakhchivan autonomous republic - Seyidova, Elnara; Salmanli, Narmin; Kara, Gülten; Ganbarova, Nurlana (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Problem Statement. Although nuclear power plants are considered to be a more economically efficient type of energy, they are considered a source of environmental danger in many respects. The Metsamor Nuclear Power Plant (Armenia) is one of the main sources of environmental risk, contributing not only to ecological problems in the area of its location within Armenia but also to transboundary impacts on neighboring countries, particularly affecting the Nakhchivan Autonomous Republic (Azerbaijan), as well as Eastern Anatolia (Türkiye), western Iran and parts of the South Caucasus (Georgia, Armenia, and Azerbaijan).The aim of this study. The aim of the study is to study atmospheric dispersion processes, The aim of the study is to assess the environmental impact of radioactive discharges, in relation to the location of MNPP reactors in a high seismic-risk border region, and to investigate the possible transport of pollutants to the Nakhchivan Autonomous Republic via air currents and the Aras River.Research Methodology. The study covers a spatial analysis of transboundary radioecological hazards in the Aras River basin, based on the collection of hydroecological samples in the field, laboratory analysis of water and ichthyofauna, geoinformation mapping, and a comprehensive assessment of seismotectonic risks. Physico-chemical, microbiological and biological parameters (pH, heavy metals, nitrates, phosphates, oxygen content, etc.) were investigated in water samples, and fish were used as bioindicators to assess the long-term accumulation of radionuclides. Furthermore, using ArcGIS (ArcMap) software, the risk factors of tectonic processes that have occurred and could occur in the area were studied, and an ecological zoning map of the Nakhchivan Autonomous Republic portion of the Aras River basin was prepared.Scientific novelty of the research. For the first time, the radiological risk associated with the Metsamor NPP has been assessed in the Nakhchivan Autonomous Republic based on an integrated regional analysis of atmospheric transport, riverine dispersion, and the biological migration of radioisotopes. In recent years, ecological zoning has been carried out and a map has been prepared, illustrating the impact of the Metsamor NPP on the Aras River basin and the Aras reservoir.The novelty of the study is characterised by the development of a spatial model of transboundary ecological risk in the Aras River basin, based on the integration of hydrochemical indicators, biotic accumulation data, and seismic hazard analysis.Results. The study determined that the main pathways of radionuclide dispersal are the Aras River, atmospheric circulation, and fish migration. Taking into account the potential dispersion of radioactive waste in the basin, the area's rivers were divided into three categories based on their ecological condition: clean, relatively clean, and highly polluted. A map compiled using ArcMap confirms the area's seismic risk, showing that hundreds of earthquakes with a maximum magnitude of 7 have been recorded in the last 45 years since the AES began operating. The environmental risk posed by the Metsamor Nuclear Power Plant to the region was determined on the basis of a comprehensive analysis of the migration pathways of radionuclides in the atmospheric, hydrographic, and biological environments, as well as an integrated assessment of hydrochemical, biotic, and seismic indicators in the Aras River basin.